PERANCANGAN SISTEM KOMPUTERISASI PENGGAJIAN DAN PENGUPAHAN PADA PERUSAHAAN PERCETAKAN - GUNAWAN, RAYMOND (: 2303-1719)
The study was conducted at PT. B.O. who engaged in printing. Company’s payroll system is less effective, so the process of payroll lcalculation contains many errors. Activity still contain many false payroll calculation, both in calculating bonuses given to employees or in wages calculations. The purpose of this research is to design a computerized payroll system that will help solve problems facing by the company. Evaluation procedures and flowcharts in the study were divided into two categories, namely employees (offices and factories) and workers (contract and wholesale). With three activities, namely the calculation of salaries and wages, payment of salaries and wages, as well as recording and reporting. With design payroll computer-based information systems, errors of calculation of salaries of employees who've been several times on a manual system can be reduced or even absent and can generate the required information quickly and accurately, and can result in reports that can be useful for management decision making.